First Report Of Fusarium Fruit Rot Causing Fusarium Incarnatum-equiseti On Amla In Bangladesh - Sikder, Md Maniruzzaman; Sultana, Aireen; Ahmmed , Md Sabbir; Alam, Nuhu (Journal of Bio-Science, 2024)
Amla (Phyllanthus emblica L.) fruit is prone to rot, which is responsible for the qualitative losses of the fruits both during the pre- and post-harvest period. A fungal pathogen was isolated using tissue planting methods. The genomic DNA of the isolated fungus was amplified and sequenced under the Sanger Sequencing platform. Blast search showed 99% sequence similarity with Fusarium incarnatum-equiseti species complex. The vegetative growth of the targeted fungus was assessed on several fungal culture media, in which Richard Agar medium exhibited the maximum mycelial growth at 25ºC temperatures. Neutral to slightly alkaline condition was mostly preferred by this fungus. Among three light regimes, the complete light condition was ideal for the mycelial growth of the fungus. Three aqueous plant extracts were evaluated to check in vitro vegetative growth, in which garlic (20%) was quite enough to restrict complete mycelial growth of it. Two food preservatives were also assessed, where sodium benzoate (50 mM) was most effective for the restriction of the targeted fungus compared to vinegar. Therefore, garlic and sodium benzoate could be used to manage the fungal growth of F. incarnatum-equiseti associated with Amla fruits. To the best of our knowledge, Amla fruit rot caused by F. incarnatum-equiseti is the first record in Bangladesh. J. Bio-Sci. 32(1): 1-12, 2024